2004
DOI: 10.1007/s11666-004-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

New material concepts for the next generation of plasma-sprayed thermal barrier coatings

Abstract: In application as a thermal barrier coating (TBC), partially stabilized zirconia (Zr) approaches some limits of performance. To further enhance the efficiency of gas turbines, higher temperature capability and a longer lifetime of the coating are needed for the next generation of TBCs. This paper presents the development of new materials and concepts for application as TBC. Materials whose compositions have the pyrochlore structure or doped Zr are presented in contrast with new concepts like nanolayers between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(42 citation statements)
references
References 28 publications
0
34
0
1
Order By: Relevance
“…3) have been developed to overcome that problem. [48,49] Thermal cycling tests of those systems have been carried out at two different surface temperatures: 1250°C and 1350°C. At the former temperature, the proposed systems improve the thermal response compared to that of the single zirconate coating, the thermal cyclic performance being similar than YSZ.…”
Section: Thermal Barrier Coatings (Tbcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…3) have been developed to overcome that problem. [48,49] Thermal cycling tests of those systems have been carried out at two different surface temperatures: 1250°C and 1350°C. At the former temperature, the proposed systems improve the thermal response compared to that of the single zirconate coating, the thermal cyclic performance being similar than YSZ.…”
Section: Thermal Barrier Coatings (Tbcs)mentioning
confidence: 99%
“…Each layer within the coating must offer a specific property, such as erosion resistance, corrosion-oxidation resistance and, naturally, thermal protection. [29,43,48] Despite there are few multilayer TBC structures developed to date, in a short-term great advances in this field are expected. Conversely, the benefits of using multilayers for EBCs have been extensively proved, the recent advances being focused in more complex systems.…”
Section: Future Outlookmentioning
confidence: 99%
“…10,11 The approach to solve this problem is likely to fabricate double layered ceramic coatings or graded ceramic coatings with the gradual change of composition in the through thickness direction with YSZ. 12 With such approach the low thermal conductivity and high phase stability of LZO could be utilised through use of YSZ with high facture toughness and relatively small thermal expansion coefficient difference with the metallic substrate. Cao et al 13 reported that double ceramic layers of thermal barrier coatings (DCL-TBCs) consisting of YSZ and LZO could significantly increase TBCs' thermal cycling lifetime at high temperature (1250uCy).…”
Section: Introductionmentioning
confidence: 99%
“…However, this standard material has a limited temperature capability due to accelerated sintering and phase transformations at high temperatures. As a result, a worldwide effort has been undertaken to identify new candidates for a TBC application [1][2][3]. It is found that, La 2 Zr 2 O 7 has excellent thermal stability, low thermal conductivity, chemical resistance, low sintering rate, and become a very promising candidate for new TBCs [4].…”
Section: Introductionmentioning
confidence: 99%